A Multi Pier (MP) method for the evaluation FRP delamination on flat and curve masonry substrates. (15th August 2022) - Zhao, Liyuan; Song, Zenghao; Feng, Hongwei; Zhao, Meng; Pirsaheb, Hiva
Abstract: In this paper a truss based approach called Multi Pier (MP) method is developed to FRP delamination on masonry substrate. According to the method, a (2D) continuous masonry element is represented via trusses assemblage consisted of two vertical elements (piers) and two diagonal rods (braces). Both axial and shear stiffness of the substrate are provided by piers and braces, respectively. Bi-linear axial behavior is dedicated to trusses based on the masonry stress–strain curve. Coupled shear-normal interaction due to curvature is considered by appropriate forces distribution among the braces. In order to validation, the approach was benchmarked against six experimental strengthened masonry pillars via C/G FRP sheets from the literature. The specimens include four flat and two curve substrates with various properties and boundary conditions under single lap shear test. For each specimen global load-slip behavior, failure mechanism, fiber tensile stress and strain profile, bond and normal (in the case of curve pillars) stresses profile during various phases of the delamination process were compared with the available experimental results. Satisfactory accuracy was obtained despite very limited computational cost due to substitution of complicated (2D) or (3D) continuous elements by simplified (1D) trusses with bi-linear axial behavior.